Human Embryonic Stem Cell Derived Mesenchymal Stromal Cells - Hematti, Peiman (2011)
Mesenchymal stromal cells (MSCs) originally isolated from bone marrow have multipotent differentiation potential, and favorable immunomodulatory and anti-inflammatory properties that make them very attractive for regenerative cellular therapy. Cells with similar phenotypic characteristics have now been derived from almost all fetal, neonatal and adult tissues; furthermore, more recently similar cells have also been generated from human embryonic stem cells (ESCs). Generation of MSCs from human ESCs provides an opportunity to study the developmental biology of human mesenchymal lineage generation in vitro. Generation of bone and cartilage from human ESC-derived MSCs and their functional characterization, both in vitro and in vivo, is also an active area of investigation as ESCs could provide an unlimited source of MSCs for potential repair of bone and cartilage defects. MSCs from adult sources are being investigated in numerous phase I-III clinical trials for a wide variety of indications, mainly based on their immunomodulatory properties. Our group and others have shown MSCs derived from human ESCs possess immunomodulatory properties similar to bone marrow-derived MSCs. Immunomodulatory properties of ESC-derived MSCs could prove to be highly valuable for their potential clinical applications in the future as derivatives of human ESCs have already entered clinical arena in the context of phase-I clinical trials.